Imbalance of intermediate filament component keratin 14 contributes to increased stress signalling in epidermolysis bullosa simplex. Issue 4 (26th March 2013) - Wagner, Martin; Trost, Andrea; Hintner, Helmut; Bauer, Johann W.; Onder, Kamil
Abstract An important characteristic of epidermolysis bullosa simplex Dowling–Meara (EBS‐DM) keratinocytes is the increased level of Jun N‐terminal kinase (JNK) stress signalling, which is thought to contribute to the disease phenotype. In this work, we report on the dramatic up‐regulation of cytokeratin 14 (K14) in the EBS‐DM model cell line KEB7 at both the transcriptional and translational levels, which is noteworthy because KEB7 patient cells are heterozygous for a missense mutation (R125P) in K14. By performing functional assays, we show a direct link between overexpressed wild‐type K14 and increased JNK signalling in healthy, immortalized keratinocytes. This observation led us to hypothesize a positive feedback model in which mutant (R125P) K14 triggers JNK signalling, leading to increased AP1‐dependent expression of K14, which in turn amplifies JNK signalling further. We therefore suggest that an imbalance of cytoplasmic K14 monomers and K14 incorporated into the intermediate filament (IF) network leads to elevated stress signalling, potentially altering IF dynamics by phosphorylation, which as a side effect, weakens EBS‐DM keratinocytes.